Conversation in Advertising at Public Radio of Denpasar City - Cokorda Istri Sri Kristina Dewi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This study aims to analyze the structure and the type of speech acts, as well as the maxims of conversation in ten adverstisement spots, aired by LPPL Public Radio of Denpasar City. Data were collected through observation, recording and note-taking. I analyzed the data qualitatively with an inductive technique. Results indicated that there were three conversation structure models srealized in the conversation broadcast on the Public Service Advertisement by LPPL Public Radio. Negative speech acts were found in nine of the advertisement spots. Quality and quantity maxims were found in nine advertisement spots too; maxim of relevance and manner were found in ten advertisement spots. The models of turn talking, adjacency pair and overall organization using positive speech acts and maxims of quality, quantity, relation and manner were required for the conversation in the advertisement. Maxim of manner plays a crucial important role in the delivery of messages. There are significant correlations of the topic with the maxims realized. These comprise turn talking model requiring positive speech acts in the maxim of quality and maxim of relevance and the adjacency pair model requiring positive speech acts that always correlate with the maxim of quantity. The overall organization model calls for positive speech acts in the conversations with maxim of manner. The negative speech acts in the conversation can use the turn talking, adjacency pair or overall organization model and can correlate with the maxim of manners.